Entities and frequency of neonatal diabetes: data from the diabetes documentation and quality management system (DPV) - Grulich-Henn, Jürgen; Wagner, V.; Thon, A.; Schober, E.; Marg, W.; Kapellen, T. M.; Haberland, H.; Raile, Klemens; Ellard, S.; Flanagan, S. E.; Hattersley, A. T.; Holl, R. W. (Diabetic medicine, 2010)
Diabet. Med. 27, 709-712 (2010) Abstract Aims The aim of this study was to elucidate the entities and the frequency of neonatal diabetes mellitus (NDM) in a large representative database for paediatric diabetes patients in Germany and Austria. Methods Based on the continuous diabetes data acquisition system for prospective surveillance (DPV), which includes 51 587 patients with onset of diabetes before the age of 18 years from 299 centres in Germany and Austria, we searched for patients with onset of diabetes mellitus in the first 6 months of life. Results Ninety patients were identified, comprising 0.17% of all paediatric cases in the DPV registry. This represented an incidence of approximately one case in 89 000 live births in Germany. A monogenic basis for NDM was established in 30 subjects (seven UPD6, 10 KCNJ11, seven ABCC8, two FOXP3, two PDX1, one INS, one EIF2AK3). Pancreatic hypoplasia or agenesis was reported in 10 patients and seven subjects were classified as having Type 1 diabetes by their centres. Transient neonatal diabetes (TNDM) accounted for approximately 10% of all cases with NDM. No aetiology was defined in 41 subjects, which may reflect incomplete genetic testing or novel genetic aetiologies. Conclusion Based on a large database, we identified a higher rate of NDM in Germany than has been reported previously. Full molecular genetic testing should be performed in all patients diagnosed before 6 months of age.
Gesehen am 31.05.2023